Reflexões sobre o conceito de práxis no fazer pedagógico de professores de Educação Física - Magalhães, Luiz Henrique Rangel (2020)
The instrument that can overcome the obstacle of the “antidialogical action” in education is the pedagogical action on promoting transformations and freedom in ourselves and others. Upon this action perspective, there is a necessity to think about the complex social reality of learners in the initial grades of Elementary school, in which they act and are inserted, so that the school doesn’t produce teaching unrelated to reality, without critical thinking. That said, this study is an investigative activity with a qualitative character, that seeks to analyze what’s the pedagogical thoughts of Physical Education teachers, data through the methodology of communicative research, in order to understand the praxis focused on social relations, ethical-political, understood as a transformation of reality. The research question is presented as follows: what’s the concept of “praxis” in the pedagogical action of Physical Education teachers in the initial grades of Elementary school of Rondonópolis/MT? And, by making this question, understanding the conception of “praxis” present in the everyday life of Elementary school Physical Education teachers from Rondonópolis, MT. Following this segment, the theme under this study was established in three axes highlighted in the following specific objectives: 1) to describe the conception of praxis of Physical Education teachers in relation to their pedagogical practices; 2) to understand the relation of the Physical Education teacher in the context of school pedagogical work; 3) to analyze what is the pedagogical thoughts of these teachers about Physical Education. The theoreticalmethodological framework chosen regards the concept of Communicative Action Theory, from the German sociologist and philosopher Jürgen Habermas, and also, the Dialogical Action Theory of Brazilian educator Paulo Freire. All informational survey was executed according the postulates of the communicative research methodology which establishes a critical communication between the researcher and participants, focusing on understanding. The methodological procedures was performed in a way that allowed the communicative observation and interviews with depth, subsidized by the chosen authors mentioned before who contributed towards the analysis of the concept of “praxis” in the pedagogical action of teachers through the information obtained; making it possible to identify the conceptions and future pedagogical practices of Physical education teachers in the initial grades of Elementary school of Rondonópolis/MT. In other words, to perceive how these teachers understand the pedagogical process within the scope of Physical Education. In the meantime, this academic work is committed to clarify the importance of pedagogical practices in the learning process of students in the initial grades of Elementary school, and also, proposing the permanent formation for a theoretical reflection that contributes to the praxis (Freire) in the perspective of communicative rationality between teachers (Habermas). We register this study in an arrangement of six chapters, seeking to correlate the statements of Habermas and Freire. Under the same point of view, a new look must be glimpsed about the matter of praxis to the pedagogical practice, given how the age range and the organism/ personality development of the student so there is a reason for the presence of Physical education in school as an integrated and contextualized component to the curriculum proposal of schools units. Therefore, this study complies with the scientific debate since it proposes discuss pedagogical thinking in the construction of dialogic-communicative actions for the promotion of all teaching work, as well as the educational process.